2008
DOI: 10.1098/rsif.2008.0156
|View full text |Cite
|
Sign up to set email alerts
|

Light alters nociceptive effects of magnetic field shielding in mice: intensity and wavelength considerations

Abstract: Previous experiments with mice have shown that repeated 1 hour daily exposure to an ambient magnetic field-shielded environment induces analgesia (antinociception). The exposures were carried out in the dark (less than 2.0!10 16 photons s K1 m K2 ) during the midlight phase of the diurnal cycle. However, if the mice were exposed in the presence of visible light (2.0!10 18 photons s K1 m K2 , 400-750 nm), then the analgesic effects of shielding were eliminated. Here, we show that this effect of light is intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Recently, we have shown that the presence of light can also attenuate the analgesia induced by repeated ELF-MF shielding in a wavelength and intensity dependence similar to that associated with geomagnetic orientation of birds and newts [Prato et al, 2009]. At that time we argued that a similar mechanism may explain both animal orientation and animal nociception effects of magnetic field exposure.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, we have shown that the presence of light can also attenuate the analgesia induced by repeated ELF-MF shielding in a wavelength and intensity dependence similar to that associated with geomagnetic orientation of birds and newts [Prato et al, 2009]. At that time we argued that a similar mechanism may explain both animal orientation and animal nociception effects of magnetic field exposure.…”
Section: Discussionmentioning
confidence: 93%
“…Also, inspection of Figure 3a and b indicates that the 25 nT exposures at 30 and 120 Hz give very different results, contrary to predictions if detection is dependent on an RPM. It is worth noting that to date, except for a recent publication from our laboratory [Prato et al, 2009], there is little evidence of a RPM in rodents [Thalau et al, 2006], although there is evidence that rodents have a magnetic compass [Muheim et al, 2006].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The initial biophysical detection mechanism of magnetoreception remains controversial, but three candidate general mechanisms exist: (i) detection by magnetic dipoles within cells and tissue; (ii) detection of an induced current; and (iii) detection via the different chemical reaction rates when the electron spins of free radicals are affected by a magnetic field. Evidence to date suggests that the effect on animal orientation is mediated by tissue dipoles and/or the free radical mechanism ( Johnsen & Lohmann 2008), while the evidence for anti-nociceptive effects may depend on several mechanisms (Thomas et al 1997;Prato et al 2000Prato et al , 2009Del Seppia et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The applied light sources emit light with several wavelength peaks between 403 and 710 nm. The calculated integral light intensity maximum corresponds to 3.9 Â 10 16 photons s 21 m 22 , which is below the intensity threshold for altering behavioural responses in mice in SMF-shielded environments [15]. The illumination conditions inside the cage were basically independent of the location of the mouse within the cage.…”
Section: Generation Of Inhomogeneous Static Magnetic Fieldmentioning
confidence: 99%